A educação ambiental na ótica da educação escolar: interfaces com uma unidade de conservação - Scheuermann, Keili Lucí Rocha (2016)
This essay aims to study the ARIE - Area of Relevant Ecological Interest as a reference for the environmental education in the public schools in the city of Santa Helena - PR. The research investigated the site of the educational managers about the guidance of environmental practices inside the classroom, seeking to find the border factors of the relationship between the human being and the environmental area. It is seen that sustainability requires a new way of environmental education, bringing from school the reassurance of how important is the relationship between the human being and ecosystem. The stated relationship is built with investments in order to qualify the environmental education in the facilities mentioned earlier. A case study was made using the data from research with the public school managers, in which interviews were used as instruments to test on how aware they were about the usage of ARIE as a privileged place to practice environmental education. The results of the studies stated that the idea of environmental education is still not well structured in the schools and doesn t make use of the resources available to enrich with knowledge and give meaning for those kinds of classes. The research also identified a low rate of motivation from the managers about the use and optimization of the conservation units. From this, it can be concluded that, within the participating schools -as an effective relationship with the ARIE didn t happen- the rupture of old paradigms must happen, in order to evoke new ways of living environmental practic classes, with which it should bring the human being in its first phase of education and the nature together, valuing the social and environmental surroundings